EFFECT OF PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) DOSES OF BAMBOO ROOTS IN DIFFERENT SOIL TYPES ON THE GROWTH AND YIELD OF Paspalum notatum - R. H. B., Tarigan; Trisnadewi, A. A. A. S.; Budiasa, I K. M. (Jurnal Peternakan Tropika, 2024)
Plant growth promoting rhizobacteria (PGPR) are a consortium of bacteria that actively colonize plant roots and thrive in soils rich in organic matter. Paspalum notatum has the advantage of being able to adapt to various types of soil, good drought tolerance, good response to nitrogen, not easily attacked by disease or disturbance by insects so it is suitable for development. This research was conducted to determine the effect and optimal concentration of PGPR on the growth and yield of Paspalum notatum grass. This study used a completely randomized design (CRD) split plot pattern with two (2) factors, were soil type as the main plot and PGPR dose as the sub-plot. The PGPR dose treatment ware: 0 ml/liter of water as a control (P1), 10 ml/liter of water (P2), and 20 ml/liter of water (P3). The types of soil used are regosol, latosol, and mediterranean soil types. The three types of soil have different textures and contents. The variables observed were growth, yield, and growth characteristics. The results showed that regosol soil types had better groeth and result than latosol and mediteran soil on the growth and yeild of Paspalum notatum. The PGPR concentration that gave the best results was the P3 treatment with a PGPR dose of 20 ml/liter of water on regosol soil. The conclution of the research that 20 ml/ liter water of PGPR and regosol type of soil give the best a growth and yeld of Paspalum notatum.